2004
DOI: 10.1111/j.1471-6712.2004.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic nursing documentation in primary health care

Abstract: The aim of this study was to describe and analyse nursing documentation based on an electronic patient record (EPR) system in primary health care (PHC) with emphasis on the nurses' opinions and what, according to the nursing process and the use of the keywords, the nurses documented. The study was performed in one county council in the south of Sweden and included 42 Primary Health Care Centres (PHCC). It consisted of a survey, an audit of nursing records with the Cat-ch-Ing instrument and calculation of frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 25 publications
(43 reference statements)
4
44
0
8
Order By: Relevance
“…There are also those that are characterized by a record of events, patient-centered care from birth to death, and have become an indispensable tool for coordination, as it ensures the interaction between all levels of system support and the continuity of care provided by health professionals. 4 At the PHC setting, the EHR is a fundamental information resource. It is the most important document that houses most of the information handled by professionals and health managers at this level of care.…”
Section: Introductionmentioning
confidence: 99%
“…There are also those that are characterized by a record of events, patient-centered care from birth to death, and have become an indispensable tool for coordination, as it ensures the interaction between all levels of system support and the continuity of care provided by health professionals. 4 At the PHC setting, the EHR is a fundamental information resource. It is the most important document that houses most of the information handled by professionals and health managers at this level of care.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an increased quality of care planning but an increased documentation workload after implementation of an NDS [27][28][29]. In a questionnaire study, including 154 nurses and performed in Swedish primary care by Törnvall et al [30], nurses' opinions on electronic documentation were generally positive. Fogelberg-Dahm and Wadensten [31] found that standardized care plans increased the nurses' abilities to provide consistent high-quality care for all patients, decreasing documentation time as well as redundancy in documentation.…”
Section: Previous Research and Evaluation Of Nursing Models And Ndssmentioning
confidence: 99%
“…Alle sjukepleiarane gjev uttrykk for å ha kompetanse på dette området, medan det blant omsorgsarbeidarane/assistentane og hjelpepleiarane syner store manglar når det gjeld å ha kunnskap om korleis dei skal skriva sjukepleieplan i Gerica. Det føreligg funn frå fleire studiar som syner at støtte og utdanningsopplegg kan betra sjukepleiedokumentasjonen [9,[12][13][14]. Nokre av desse studiane har føregått over lang tid, der pre-og post-test av sjukepleiedokumentasjonen syner signifikante forbetringar etter opplaering [11][12][13][14].…”
Section: Diskusjonunclassified